Comparative Distribution of Small Mammals Diversity in Protected and Non-Protected Area of Peninsular Malaysia - Julius William-Dee,; Faisal Ali Anwarali Khan,; Qhairil Rosli,; Muhd Amsyari Morni,; Isham Azhar,; Lee Sim Lim,; Roberta Chaya Tawie Tingga,; Mohd Ridwan Abdul Rahman, (Tropical Life Sciences Research, 2019)
Rapid urbanisation in Malaysia has led to an increase in anthropogenic activities, inducing degradation of the natural environment. This advocates the necessity of wildlife and resource inventories be conducted at available forested areas, promoting steady improvement in the existing conservation and management plans, especially for threatened taxa such as the small mammals. Small mammals surveys was conducted at Tasik Bera, Ulu Gombak Forest Reserve, Sungkai Wildlife Conservation Centre, Penang Island, and Wang Kelian State Park. Harp traps, mist-nets, cage traps and pitfall traps were set during the surveys. Rhinolophus affinis was the most abundant (N = 61) volant small mammal, followed by Rhinolophus lepidus (N = 27). Meanwhile, the most abundant non-volant small mammal are Leopoldamys sabanus (N = 33), followed by Maxomys rajah (N = 25), and Tupaia glis (N = 22). Two species of shrews, Suncus etruscus and Crocidura monticola were caught as singletons. The results indicated that Ulu Gombak Forest Reserve has the highest species diversity (H’ = 2.754), whereas Penang Island recorded the lowest (H’ = 2.245). The species lists of small mammals generated from the survey will be significant for various stakeholders’ conservation and monitoring plans. Pembangunan yang semakin pesat di Malaysia telah meningkatkan bilangan aktiviti antropogenik, sekaligus menyebabkan kemerosotan alam sekitar. Ini menunjukkan bahawa perlunya inventori hidupan liar dan sumber alam sekitar dijalankan di dalam kawasan hutan yang sedia ada, untuk mempromosikan peningkatan yang seimbang dalam pelan pemuliharaan dan pengurusan yang sedia ada, terutamanya untuk haiwan yang terancam seperti spesies mamalia kecil. Kajian mamalia kecil telah dijalankan di Tasik Bera, Hutan Simpan Ulu Gombak, Pusat Konservasi Hidupan Liar Sungkai, Pulau Pinang, dan Taman Negeri Wang Kelian. Harp trap, mist net, cage trap dan pitfall trap telah dipasang untuk kajian. Spesies Rhinolophus affinis (N = 61) merupakan spesies yang paling banyak ditangkap, diikuti dengan R. Lepidus (N = 27). Manakala untuk mamalia kecil tidak terbang, species Leopoldamys sabanus merupakan spesies paling banyak (N = 33) diikuti dengan Maxomys rajah (N = 25) dan Tupaia glis (N = 22). Dua spesies cencurut, Suncus etruscus dan Crocidura monticola masing-masing telah ditangkap dengan jumlah satu individu bagi setiap satu spesies. Hutan Simpan Ulu Gombak merekodkan kepelbagaian spesies yang paling tinggi (H’ = 2.754), manakala Pulau Pinang merekodkan nilai yang paling rendah (H’ = 2.245). Senarai mamalia kecil yang telah direkodkan melalui kajian ini merupakan maklumat yang signifikan bagi tujuan pemantauan dan konservasi biodiversiti.